PENYULUHAN TENTANG TATA CARA MEMBUAT PERATURAN PERUSAHAAN DI PT. PELANGI WARNA KREASI BANDUNG - Zulkarnaen, Ahmad Hunaeni (JE (Journal of Empowerment), 2017)
Employers who hire at least 10 (ten) employees shall make a company regulation. A company regulation is a written rule made by the employer which contains the terms of employment and the rules of the company. In the rule-making companies need continually to do under the technical guidance in order to gain the company rules that provide a protection for workers. Rule-making company is the employersâ€™ responsibility, which is in the drafting process should heed the advice and judgment of representatives of workers or from labor unions.Â